A natural strategy for astaxanthin stabilization and color regulation: Interaction with proteins. (15th February 2023) - Yao, Qimeng; Ma, Jiaqi; Chen, Xuemin; Zhao, Guanghua; Zang, Jiachen
Graphical abstract: Highlights: The low stability of astaxanthin limits its application as a bioactive factor. Algae, fish and crustaceans in nature stabilize astaxanthin by binding to proteins. Structure and physicochemical properties of proteins affect its binding capacity. Conformational changes of astaxanthin in protein complex cause species color changes. Inspiration from nature provides advanced strategies for utilization of astaxanthin. Abstract: The pigment astaxanthin, one of the carotenoids, is regarded as a functional factor with various biological activities, widely applied in feed, nutraceutical, and cosmetic industries. However, its low stability and poor water solubility limit its application. Examples in nature suggest that binding to proteins is a simple and effective method to improve the stability and bioavailability of astaxanthin. Proteins from algae, fish, and crustaceans have all been demonstrated to have astaxanthin-binding capacity. Inspired by nature, artificial astaxanthin-protein systems have been established in foods. Binding to proteins could bring aquatic species various colors, and changes in the conformation of astaxanthin after binding to proteins leads to color changes. The review innovatively summarizes multiple examples of proteins as means of protecting astaxanthin, giving a reference for exploring and analyzing pigment-protein interactions and providing a strategy for carotenoids stabilization and color regulation, which is beneficial to the broader and deeper applications of carotenoids.